The role of arbitration in resolving maritime transport disputes a comparative study - Abdulbaqi Yusef , Assist .Prof. Itidal; Fawzi Gatii, Lect. Zaman (Basra studies journal, 2023)
Many disputes arise during the conduct of the maritime transport process between the parties to this process, and these disputes are resolved either by resorting to the judiciary or by resorting to alternative methods of dispute resolution. The way of agreement between the parties to refer the disputes that arise between them, whether current or future, to an arbitrator or an arbitral tribunal. Maritime arbitration is one of the oldest alternative means for resolving maritime disputes. The arbitration agreement derives its strength from the will of the contracting parties. To clarify the importance of arbitration in the scope of maritime transport, we will discuss the nature of maritime arbitration, in addition to the procedures and effects of resorting to arbitration in the scope of maritime transport.